(untitled) (Bangladesh Medical Journal, 2021)
Type 1 diabetes mellitus is one of the most common endocrine and metabolic disorder in children and adolescents. Alteration of serum magnesium level may be associated with metabolic control and diabetic complications. The aim of the study was to evaluate serum magnesium level and find out its relationship with glycemic control in type 1 diabetic children and adolescents. For this study 80 type 1 diabetic children & adolescents with age range 1 to 18 years and 80 aged matched healthy controls were enrolled from the outpatient department of Changing Diabetes in Children, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine & Metabolic disorders, General Hospital, Dhaka. Using a cross sectional design, we measured anthropometric parameters and serum magnesium level of all study subjects. We also estimate the fasting plasma glucose and HbA1c levels of the diabetic children and adolescents and controls. The mean ± SD of serum magnesium level was significantly lower in patient with type 1 DM compared to control (0.7 ± 0.1 vs 0.8 ± 0.1 mmol/L respectively; p= < 0.001). Lower level of magnesium was found in subjects with poor glycemic control compared to good glycemic control (0.6 ± 0.1 vs 0.8 ± 0.1 mmol/L respectively; p= < 0.001). This study showed that serum magnesium level was lowered in type 1 diabetic children and adolescents and it was strongly associated with poor glycemic control which potentially contributing to the early development of diabetic complications. Bangladesh Med J. 2019 Sep; 48 (3): 16-20